Transition of care in pediatric oncohematology: a systematic literature review - Strini, Veronica; Daicampi, Chiara; Trevisan, Nicola; Marinetto, Anna; Prendin, Angela; Marinelli, Elena; de Barbieri, Ilaria (Acta Biomedica Atenei Parmensis, 2020)
Background: The transition of medical care from a pediatric to an adult environment is a psychological change, a new orientation that requires a self-redefinition of the individual, to understand that changes are taking place in his life. Up to 60 percent of pediatric patients who transition to adult services will experience one or more disease or treatment-related complication as they become adults. A nurse who knows how to recognize potential barriers at an early stage can play a pivotal role in the educational plan for the transition process. Materials and methods: A literature search was undertaken of PUBMED, CINAHL and The Cochrane Library, with specific inclusion and exclusion criteria, including articles published in the lasts ten years.This literature review has been performed according to the PRISMA statement. Results: Using the keywords in different combination 38 articles were found in The Cochrane Library, 5877 in PUBMED, 274 in CINAHL. 88 articles were selected after the abstract screening. 31 after removing the duplicates and reading the full text. Discussion: The main themes surrounding transition of care that emerged from the synthesis are the organization of care within common models of transition, innovative clinical approaches to transition, and the experience of patients and caregivers. The transition from pediatric to adult care of cancer or SCD survivors is an emerging topic in pediatric nursing. The organization of care is affected by the lack of clear and well-structured organizational models. Further research is needed to deepen the understanding of some aspects of the transition.